Diversity Of Nocturnal Insects (Insecta) In Bukik Kasang, Padang Pariaman, West Sumatra - Emelia Debora; Rijal Satria (Bioscience, 2019)
The study of nocturnal insect diversity was conducted in Bukik Kasang, Padang Pariaman District, West Sumatra from April to May 2019. The pitfall trap was used to collect the active insect on the ground in three different habitats: open area, edge of plantation, and inside the plantation. A total 10 orders, 44 morphospecies, and 180 individual of nocturnal insect was collected. The Order Hymenoptera was the highest in number of morphospecies and individual, and in other hand, the Order Hemiptera was the lowest one. This study is very important to reveal the diversity of insect in Bukik Kasang, due to the increasing of human activities in this area and planning to develope this area as tourist destination.